Effect of Sintering Temperature on Percentage of Tetragonal And Rhombohedral On Comparison of Zr / Ti (60/40) - Tamam Abimanyu; Rachmat Triandi; Masruroh Masruroh (Natural B, Journal of Health and Environmental Sciences, 2015)
The synthesis of lead zirconate titanate (PZT) with ratio Zr:Ti of 60:40 have been conducted by sol gel method. The precursor of PZT were prepered from zirconium(IV) nitrate pentahydrate, titanium(IV) butoxide, lead(II) acetate trihydrate and 2-methoxyethanol and acetylaceton as a stabilizer solution. The PZT films deposited on Si substrate by spin coating method, then it was sintered at different temperature of 500°C, 600°C and 700°C. The crystal structure and composition of PZT films were observed by X-ray Diffraction (XRD) and Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDX). The XRD results show the crystal orientation of PZT (100), (101), (110), (111), (002)T, (200)R, (200)T, (201) and (210), means that all PZT films are polycrystalline. Moreover, the orientation of (110) as temperature sintered of 600°C show the highes intensity than other temperature. The EDX results show mole fraction of Zr and Ti decrease compound with iniatial precursor. On the other hand, the mole fraction of O increase, which result in the existence of ZrO2 and TiO2 crystal.